The prognostic value of Tei index in acute myocardial infarction: a systematic review. Issue 4 (December 2020) - Bennett, Sadie; Wong, Chun Wai; Griffiths, Timothy; Stout, Martin; Khan, Jamal Nasir; Duckett, Simon; Heatlie, Grant; Kwok, Chun Shing
Abstract : Background: Echocardiographic evaluation of left ventricular ejection fraction (LVEF) is used in the risk stratification of patients with an acute myocardial infarction (AMI). However, the prognostic value of the Tei index, an alternative measure of global cardiac function, in AMI patients is not well established. Methods: We conducted a systematic review, using MEDLINE and EMBASE, to evaluate the prognostic value of the Tei index in predicting adverse outcomes in patients presenting with AMI. The data was collected and narratively synthesised. Results: A total of 16 studies were including in this review with 2886 participants (mean age was 60 years from 14 studies, the proportion of male patients 69.8% from 14 studies). Patient follow-up duration ranged from during the AMI hospitalisation stay to 57.8 months. Tei index showed a significant association with heart failure episodes, reinfarction, death and left ventricular thrombus formation in 14 out of the 16 studies. However, in one of these studies, Tei index was only significantly predictive of cardiac events in patients where LVEF was <40%. In two further studies, Tei index was not associated with predicting adverse outcomes once LVEF, left ventricular end-systolic volume index and left ventricular early filling time was taken into consideration. In the two remaining studies, there was no prognostic value of Tei index in relation to patient outcomes. Conclusions: Tei index may be an important prognostic marker in AMI patients, however, more studies are needed to better understand when it should be used routinely within clinical practice.